Implementation of Zoning System Policy in the Admission of New Students at State High School 115 Jakarta - Mufliha, Septi; Wijayanto, Hendra; Firman; Prasetyo, Sisman (Yayasan Mentari Madani, 2024)
The purpose of this study was to determine how the implementation of the zoning system policy on the acceptance of new students (PPDB) in SMA Negeri 115 Jakarta and obstacles to the implementation of the zoning system policy on the acceptance of new students (PPDB) in SMA Negeri 115 Jakarta. This study is descriptive research with a qualitative approach. The subjects were principals, PPDB Implementation Committee, students and parents. Data collection methods used are observation, interview and documentation. The results showed that: (I) in its implementation based on the principles of objective policy, transparent, accountable and non-discriminatory.in the field according to the principle of transparency has not been done maximally (II) socialization of zoning system policies in the acceptance of new learners conducted by the school to the target group through social media, however, the socialization has not been fully maximized (III) the implementation of the zoning system policy in PPDB at SMA Negeri 115 Jakarta in terms of human resources and non-human resources is very sufficient to support all activities in the implementation of the policy (IV) the disposition of the implementor in the implementation of the zoning system policy has been very good (V) the bureaucratic structure of SMA Negeri 115 Jakarta in the implementation of the zoning system for the acceptance of new students is quite good seen from the division of labor in the PPDB committee